2016
DOI: 10.5194/isprsarchives-xli-b4-227-2016
|View full text |Cite
|
Sign up to set email alerts
|

The Urbis Project: Identification and Characterization of Potential Urban Development Areas as a Web-Based Service

Abstract: ABSTRACT:Urban sprawl and the related landscape fragmentation is a Europe-wide challenge in the context of sustainable urban planning. The URBan land recycling Information services for Sustainable cities (URBIS) project aims for the development, implementation, and validation of web-based information services for urban vacant land in European functional urban areas in order to provide end-users with site specific characteristics and to facilitate the identification and evaluation of potential development areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Thus, the existing techniques only generate information on potential brownfield sites, and manual field verifications are essential in a post-processing step to eliminate false positives. Additionally, a project that aimed to develop 'Urban Land Recycling Information Services for Sustainable Cities' (Moser et al 2015;Manzke et al 2016) came to the conclusion that the detection of brownfield sites using available satellite images and the Urban Atlas alone was nearly impossible (Manzke et al 2016).…”
Section: Previous Approaches Towards the Automated Detection Of Idpmentioning
confidence: 99%
“…Thus, the existing techniques only generate information on potential brownfield sites, and manual field verifications are essential in a post-processing step to eliminate false positives. Additionally, a project that aimed to develop 'Urban Land Recycling Information Services for Sustainable Cities' (Moser et al 2015;Manzke et al 2016) came to the conclusion that the detection of brownfield sites using available satellite images and the Urban Atlas alone was nearly impossible (Manzke et al 2016).…”
Section: Previous Approaches Towards the Automated Detection Of Idpmentioning
confidence: 99%
“…To overcome the limitations of these approaches, methods for the automatic detection of IDPs are needed to help monitor at the national level as well as deliver basic knowledge on the local level at little expense (Schiller et al 2021;Xu & Ehlers 2022). Although some attempts for automatic detection of brownfields based on remote sensing were made (Atturo et al 2006;Ferrara 2008;Manzke et al 2016;Xu & Ehlers 2022) and the use of artificial intelligence is promising (Dürrbeck & Lippl-Seifert 2022), until now no approaches have included small-scale IDP. Hecht & Meinel (2014) proposed a GIS-based approach using topographical and building data, but concluded that the results greatly overestimate the infill potential due to missing lot boundaries and only coarse differentiation of land use.…”
Section: Introductionmentioning
confidence: 99%